CHEMICAL PROFILE OF TWO JASMINUM SAMBAC L. (AIT) CULTIVARS CULTIVATED IN EGYPT–THEIR MEDIATED SILVER NANOPARTICLES SYNTHESIS AND SELECTIVE CYTOTOXICITY - EL-HAWARY, SEHAM S.; EL-HEFNAWY, HALA M.; OSMAN, SAMIR M.; MOSTAFA, EMAN S.; MOKHTAR, FATMA ALZAHRAA; EL-RAEY, MOHAMED A. (International Journal of Applied Pharmaceutics, 2019)
Objective: Evaluation of two Jasminum sambac L. (Ait) cultivars; Arabian Nights (JSA) and Grand Duke of Tuscany (JSG) ethanolic leaves extracts as reducing agents for the green synthesis of silver nanoparticles (AgNPs) and evaluation of their cytotoxicity against MCF-7 breast cancer and 5637 bladder cancer cell lines and chemical profiling of the two cultivars. Methods: The synthesis of silver nanoparticles (AgNPs) by the two cultivars and characterization of AgNPs by ultraviolet (UV)–visible spectroscopy, Transmission electron microscopy (TEM) and Fourier Transform Infrared Spectroscopy (FTIR). Additionally, the use of The high-performance liquid chromatography coupled with photodiode array-mass-mass-spectroscopy (HPLC-PDA-MS/MS) for chemical profiling of both cultivars and evaluation of total leaves extracts and corresponding nanoparticles towards MCF-7 and 5637 cell lines compared to aneuploidy immortal keratinocyte (Ha Cat) normal cells by neutral cell assay. Results: The green synthesized AgNPs (of an average size range of 8.83 and 11.24 nm for JSA and JSG, respectively) exhibited cytotoxicity against MCF-7 and 5637 cell lines. The IC50 was determined for each total extract JSA (15.29±2.16 μg/ml) and JSG (20.28±1.20 μg/ml) and corresponding AgNPs 17.32±2.22 μg/ml and 6.32±1.01μg/ml for JSA and JSG, respectively. The IC50 of JSA and JSG against 5637 bladder cancer cell line were 13.76±1.11 μg/ml and 50.69±3.75 μg/ml, while the corresponding AgNPs showed IC50 of 5.54±0.88 μg/ml and 27.89±2.84 μg/ml, respectively. The HPLC-PDA-MS/MS allowed the identification of 59 compounds; 10 simple phenols, 17 flavonoids; quercetin and kaempferol glycosides, 2 lignans, and 30 secoiridoids; oleuropein, molihauside, and sambacoside. Conclusion: This study proved that JSA is an excellent source for the synthesis of AgNPs with optimum characters and enhanced activities toward MCF-7 and 5637 cell lines in correlation to identified compounds.